SOME MACROFUNGI FROM PHULCHOWKI AREA OF KATHMANDU VALLEY, NEPAL - Jha, Sanjay Kumar; Tripathi, N. N. (Ecoprint: An International Journal of Ecology, 2013)
During present study, a survey was made from Godavari to Phulchowki, Kathmandu valley up to the height of 2250 m. in order to collect macrofungi with special reference to habit, habitat, substrate and ethnobotanical information. The species were brought to laboratory and identified through morphological and microscopic examination. Out of 45 macrofungi species collected, 20 species belonging to 13 families were identified. The major species were Agaricus silvicola, Amanita caesarea, Bovista plumbea, Clavulina cristata, Clavulinopsis fusiformis etc. The detailed measurement of pileus and stipes, colour of pileus, gills and stipes, cap profiles, stem profiles, spore structure were done. DOI: http://dx.doi.org/10.3126/eco.v18i0.9396 Ecoprint: An International Journal of Ecology Vol. 18, 2011 Page: 33-38 Uploaded date: 12/20/2013